The Hunger Games: laparoscopic performance in novice surgeons is not altered by food deprivation but influenced by the degree of appetite : a randomized controlled trial - Bechtolsheim, Felix, Freiherr von; Oehme, Florian; Weitz, Jürgen; Oppermann, Nadine; Reißfelder, Christoph; Mees, Sören Torge; Yang, Cui (Journal of surgical education, 2020)
OBJECTIVES - Food deprivation is a common condition for visceral surgeons and especially laparoscopic approaches require high levels of concentration. The current literature does not provide adequate answers whether intraoperative breaks, especially food intake, might influence the quality of the surgical skills. Thus, the primary aim of this trial was to analyze the influence of food deprivation on the laparoscopic performance. - DESIGN SETTING AND PARTICIPANTS - 37 laparoscopic novices participated from 10/2017 to 04/2018 in this single center, prospective-randomized trial and were trained during laparoscopic training sessions until they reached a predefined level of proficiency. Subsequently, participants were randomized into 3 different groups: food deprivation of 8 hours, 4 hours, or carbohydrate loading directly prior to the laparoscopic exam. The exam comprised PEG-transfer, precise cutting, gallbladder resection and surgical knot. - MAIN FINDINGS - Completion time for PEG-transfer, precise cutting, gallbladder resection and surgical knot was 63s, 139s, 192s and 272s respectively. Participants starving for 8 hours performed 3 of 4 tasks more slowly whilst participants starving for 4 hours performed 3 of 4 tasks faster than the average. Analyzing self-reported level of appetite revealed: Students with an intermediate level were significantly faster (p <0.05) during complex procedures compared to participants that reported hunger prior to performing these tasks (192s vs. 307s). Additionally, hungry students had been more inaccurate during the surgical knot (p <0.05) whilst students with intermediate appetite level tend to be most accurate (p - value 0.012). - CONCLUSIONS - The subjective level of appetite rather than the absolute number of fasting hours influences the laparoscopic performance most. Thus, any extreme level of appetite may be avoided and surgeons may achieve the best performance when they have an intermediate level of appetite. In consequence, heavy meals may be omitted immediately prior to demanding laparoscopic procedures and surgeons may have access to mini-breaks and refreshers during major procedures.